2014
DOI: 10.7601/mez.65.139
|View full text |Cite
|
Sign up to set email alerts
|

Bio-efficacy, user perception and acceptability of pyrethroid based mosquito coils in controlling <i>Anopheles gambiae</i> s.l., in some parts of Accra, Ghana

Abstract: Abstract:This study was to provide baseline information on patterns of coil usage, user acceptability and susceptibility levels of mosquito coils in some parts of Accra, Ghana. Three hundred and twenty questionnaires were administered to obtain information on knowledge and perception of respondents on the usage of mosquito coils. Adult Anopheles gambiae mosquitoes were tested for resistance to pyrethroid based mosquito coils using WHO standard protocol for testing household insecticide products. A total of 152… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…With the wide spread of pyrethroid resistance among the Culex species observed in this study there is a need to evaluate the efficacy of these strategies. Already, a recent study has observed a reduced bio-efficacy of mosquito coils against pyrethroid-resistant A. gambiae in Ghana (Adu-Acheampong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With the wide spread of pyrethroid resistance among the Culex species observed in this study there is a need to evaluate the efficacy of these strategies. Already, a recent study has observed a reduced bio-efficacy of mosquito coils against pyrethroid-resistant A. gambiae in Ghana (Adu-Acheampong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%